1995
DOI: 10.1074/jbc.270.51.30264
|View full text |Cite
|
Sign up to set email alerts
|

Stat1 Depends on Transcriptional Synergy with Sp1

Abstract: STAT (signal transducer and activator of transcription) proteins combine with cytokine receptors and receptor-associated kinases in distinct protein/protein interactions that are critical for STAT-dependent signal transduction events, but the nature of any subsequent STAT interactions with DNA-binding proteins in the nucleus is less certain. Based on assays of DNA/protein binding and activity of transfected reporter plasmids, we determined that occupation of contiguous DNA-binding sites for Stat1 (the first me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
158
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(166 citation statements)
references
References 35 publications
7
158
1
Order By: Relevance
“…In addition, studies using polyclonal antibodies to either the amino-terminal or the carboxyl-terminal portions of Stat1␣ appear to exclude Stat1␤ as a possible component of the GRF complex. These data are in agreement with the recently reported GAFlike factor binding to the IFN␥RE of ICAM-1 gene (39) and the recent finding of Stat1␣ involvement in the complex by immunoblotting using anti-Stat1 antibodies (40). Previous reports indicate that Stat1␣ is a common component of the IFN-activated trans-acting complexes GAF and ISGF3.…”
Section: Icam-1 Gene Induction By Ifn␥ Via a Distinct Stat Complexsupporting
confidence: 82%
“…In addition, studies using polyclonal antibodies to either the amino-terminal or the carboxyl-terminal portions of Stat1␣ appear to exclude Stat1␤ as a possible component of the GRF complex. These data are in agreement with the recently reported GAFlike factor binding to the IFN␥RE of ICAM-1 gene (39) and the recent finding of Stat1␣ involvement in the complex by immunoblotting using anti-Stat1 antibodies (40). Previous reports indicate that Stat1␣ is a common component of the IFN-activated trans-acting complexes GAF and ISGF3.…”
Section: Icam-1 Gene Induction By Ifn␥ Via a Distinct Stat Complexsupporting
confidence: 82%
“…Other transcription factors known to bind to the p27 promoter are Sp1, NF-kB, and Myb (Kwon et al, 1996). Furthermore, it was shown that Sp1 and STAT1 synergize in interferon-g-induced responses (Look et al, 1995), while synergy between Sp1 and STAT3 was demonstrated in interleukin 6-induced transcription of the CCAAT/enhancer binding protein d (Cantwell et al, 1998). These factors therefore represent additional candidates for facilitating the observed transcriptional e ects of STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…In that respect, some Stat proteins bind to other transcription factors or coactivators to activate transcription (Bhattacharya et al, 1996;Look et al, 1995;Muhlethaler-Mottet et al, 1998;Qureshi et al, 1995;Schaefer et al, 1995;Shen and Stavnezer, 1998;Zhang et al, 1996). More speci®cally, MGF/Stat5a has only been reported to form a complex with the glucocorticoid receptor (GR) on the b-casein promoter devoid of GR binding site (GRE) (Cella et al, 1998;StoÈ cklin et al, 1996).…”
Section: Introductionmentioning
confidence: 99%